Bringing Inclusion into Focus: A Camp-based Research Study. Issue 2 (3rd April 2019) - Uhrman, Abigail L.; Walton, Ginger; Oakes, Lindsey; Schleien, Stuart J.; Kress, Jeffrey S.
ABSTRACT: As an increasing number of Jewish summer camps welcome campers with disabilities, it becomes more important to understand the experience of these campers and that of their neurotypical peers. In this study, campers with disabilities and neurotypical campers participated together in a photography activity. Photographs and their accompanying narratives were analyzed, yielding three categories of results: (1) camp community and responsibility (2) Jewish experience at camp; and (3) challenges and opportunities. Results are discussed in terms of enhancing the experience of inclusion at camp for all campers.